Tracking auditory mismatch negativity responses during full conscious state and coma - Herrera-Diaz, Adianes; Boshra, Rober; Tavakoli, Paniz; Lin, Chia-Yu A.; Pajankar, Netri; Bagheri, Elham; Kolesar, Richard; Fox-Robichaud, Alison; Hamielec, Cindy; Reilly, James P.; Connolly, John F. (Frontiers in Neurology, 2023)
The mismatch negativity (MMN) is considered the electrophysiological change-detection response of the brain, and therefore a valuable clinical tool for monitoring functional changes associated with return to consciousness after severe brain injury. Using an auditory multi-deviant oddball paradigm, we tracked auditory MMN responses in seventeen healthy controls over a 12-hour period, and in three comatose patients assessed over 24 hours at two time points. We investigated whether the MMN responses show fluctuations in detectability over time in full conscious awareness, or whether such fluctuations are rather a feature of coma. Three methods of analysis were utilized to determine whether the MMN and subsequent event-related potential (ERP) components could be identified: traditional visual analysis, permutation t-test and Bayesian analysis. The results showed that the MMN responses elicited to the duration deviant-stimuli are elicited and reliably detected over the course of several hours in healthy controls, at both group and single-subject levels. Preliminary findings in three comatose patients provide further evidence that the MMN is often present in coma, varying within a single patient from easily detectable to undetectable at different times. This highlights the fact that regular and repeated assessments are extremely important when using MMN as a neurophysiological predictor of coma emergence.